PENERAPAN STRATEGI GENERATIVE LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 10 PADANG TAHUN PELAJARAN 2012-2013 - Syafriana, Neneng Aulia; Rahmi, Rahmi; Pratiwi, Merina (Pendidikan Matematika, 2013)
This research are  motivated by the lack of teachers who raise students  knowledge to express opinions / ideas regarding the content to be learned. One method to overcome this problem is to adopt a strategy of Generative Learning. This study aims to determine the students understanding of mathematical concepts using Generative Learning Strategy was  understanding of mathematical concepts was better  than students who used conventional teaching seventh grade students of SMP Negeri 10 Padang. This type of research is experimental research study design for subjects randomized. The study population was all students in class VII SMP Negeri 10 fields listed in the school year 2012/2013. Random sampling technique and terplih VIIg class as the experimental class and the control class as a class VIIe. The research instrument is essay test with a reliability test was 0.90. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples. Hypothesis test results obtained P-value <α. Thus, it can be concluded that the students understanding of mathematical concepts using Generative Learning strategies are better than student understanding of mathematical concepts with conventional teaching seventh grade students of SMP Negeri 10 Padang.